Balanced Scorecard sebagai Pengukuran Kinerja Koperasi Perikanan Segaraning Harum Kabupaten Badung - Septiasari, Melita Isti; Darmawan, Dwi Putra; Suarthana, I Wayan (JURNAL MANAJEMEN AGRIBISNIS (Journal Of Agribusiness Management), 2015)
The Balanced scorecard is used to measure performance by observing the balance between financial and non financial side between short term and long term as well as involving the internal and external factors. The cooperative as a business entity is expected to implement the balanced scorecard to achieve the vision and mission of cooperation and improving the performance of cooperatives. The purpose of this research was to analyze the application of the four elements of the balanced scorecard which is expected to create cooperatives to compete with other economic institutions. This research was conducted with descriptive method to describe the application of the balanced scorecard element for a month in the Save unit borrow Cooperative Fisheries Segaraning Harum. The results showed the application of elements of a financial perspective using the current ratio, total assets to debt ratio rated very unhealthy and return on asset were judged enough healthy. Application of the elements of the perspective of customers using the level of customer satisfaction rated satisfied customer retention rate and are rated good. Application of the elements of the internal business processes perspective measured using Manufacturing Cycle Efficiency (MCE), namely the process of transaction deposits and loans rated has been running efficiently. Application of the elements of the learning and growth perspective employees using employee satisfaction level of votes satisfied the employee retention rate and are rated good Suggestionsfrom this researchthat thebalanced scorecardelementscan not only beusedas a measureof performancein theSegaraningHarumCooperative Fisheriesbutalsoas a strategy ofthe cooperative.Balancedscorecardshould begin tobe appliedas a measureof performanceineach ofthe cooperativein order to competewithother economicinstitutions . Apart fromcooperatives,the governmentis expected toissue a policythatbalanced scorecardused asa strategyrequired to beimplementedby the cooperative.
Keywords: application element, the balanced scorecard, cooperative